A potential therapeutic approach for ulcerative colitis: targeted regulation of mitochondrial dynamics and mitophagy through phytochemicals - Zhou, Jianping; Xi, Yuting; Wu, Ting; Zeng, Xiaoyu; Yuan, Jun; Peng, Lei; Fu, Hao; Zhou, Ce (Frontiers in Immunology, 2025)
Mitochondria are important organelles that regulate cellular energy and biosynthesis, as well as maintain the body’s response to environmental stress. Their dynamics and autophagy influence occurrence of cellular function, particularly under stressful conditions. They can generate reactive oxygen species (ROS) which is a major contributor to inflammatory diseases such as ulcerative colitis (UC). In this review, we discuss the key effects of mitochondrial dynamics and mitophagy on the pathogenesis of UC, with a particular focus on the cellular energy metabolism, oxidative stress, apoptosis, and immunoinflammatory activities. The therapeutic efficacy of existing drugs and phytochemicals targeting the mitochondrial pathway are discussed to reveal important insights for developing therapeutic strategies for treating UC. In addition, new molecular checkpoints with therapeutic potential are identified. We show that the integration of mitochondrial biology with the clinical aspects of UC may generate ideas for enhancing the clinical management of UC.